HUBUNGAN KADAR MAGNESIUM DENGAN VOLUME HEMATOMA DAN DERAJAT KLINIS PASIEN PERDARAHAN INTRASEREBRAL - Bhetaria Santoso; Amiruddin Aliah; Susi Aulina (PERDOSNI, 2020)
Introduction: High serum magnesium levels at hospital admission are associated with a small volume of incoming hematoma with a lower National Institutes of Health Stroke Scale (NIHSS) score. Aim: To assess the correlation between the serum magnesium levels, the hematoma volume, and the clinical degree in patients with acute supratentorial intracerebral hemorrhagic stroke. Methods: The study used a cross-sectional design of acute supratentorial intracerebral hemorrhagic stroke patients whose the levels of serum magnesium and clinical stroke degrees were examined using the NIHSS from January 2018 through April 2019 at Wahidin Sudirohusodo Hospital, Makassar. Results: There were 32 subjects (18 male, 14 female) obtained in this research with average age of 55.81+0.496 and average level of serum magnesium 1.9244+0.49657mg/dL. The results indicated that there was a significant correlation between serum magnesium levels and the hematoma volume and clinical degree in patients with acute supratentorial intracerebral hemorrhagic stroke. Through the Spearman correlation test, it was found that serum magnesium levels were correlated negatively and linearly with hematoma volume and NIHSS acute supratentorial intracerebral hemorrhagic stroke patients. Discussion: There was a significant correlation between serum magnesium levels, hematoma volume and clinical degree in patients with acute supratentorial intracerebral hemorrhagic stroke. Keywords: Acute intracerebral hemorrhage stroke, clinical degree of stroke (NIHSS), hematoma volume, serum magnesium level